2005
DOI: 10.1055/s-2005-864219
|View full text |Cite
|
Sign up to set email alerts
|

Five Years Later: Language in School-Age Internationally Adopted Children

Abstract: This study followed a cohort of 46 school-age children adopted from Eastern Europe who were originally studied by Glennen and Masters up through age 2 or 3. Five years later, the children were 6 to 9 years of age. Data on their school-age abilities were collected through surveys of parents and teachers. Parents indicated that 17.4% of the children were receiving classroom accommodations or special education programs and 54.5% had one or more diagnoses. The most common diagnosis was attention deficit disorder/a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
3
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 13 publications
6
49
3
3
Order By: Relevance
“…12.5% of the general population of Eastern Europe). This percentage is lower than the percentage observed by other authors -25% (Glennen & Bright, 2005), 42% (Beverly et al, 2008) and 46% (Miller et al, 2009) -but it is higher than the prevalence for ADHD in the general population (3-10%).…”
Section: Insert Table 3 About Herecontrasting
confidence: 52%
See 1 more Smart Citation
“…12.5% of the general population of Eastern Europe). This percentage is lower than the percentage observed by other authors -25% (Glennen & Bright, 2005), 42% (Beverly et al, 2008) and 46% (Miller et al, 2009) -but it is higher than the prevalence for ADHD in the general population (3-10%).…”
Section: Insert Table 3 About Herecontrasting
confidence: 52%
“…Knowing that the prevalence of this disorder is 3-10% in general population, a higher proportion of this label was observed among children adopted from Eastern Europe in these studies: 25% (Glennen & Bright, 2005), 42% (Beverly, McGuinness, & Blanton, 2008) and 46% (Miller, Chan, Tirella, & Perrin, 2009). Unfortunately none of these three studies included a sample of children adopted from other countries, in order to compare the results of children adopted form Eastern Europe countries.…”
Section: Adhd Symptoms In Internationally Adopted Childrenmentioning
confidence: 93%
“…However, her detailed language testing revealed that 11.4% of children had speech language impairment at age 6-9 years. Use of context, social relations, and nonverbal communication were relative areas of weakness [59], areas which we did not specifically test. Our findings of nearly universal strong language skills may have reflected the entry criteria for our study, in which children with specific difficulties were excluded.…”
Section: Discussionmentioning
confidence: 99%
“…It is also notable that the age of adoption is not necessarily predictive of later school age problems. In general, the language of typical IA children catches up with their non-adopted peers by ages 3-4 years and continues to develop at a normal rate throughout their school-age years (Glennen & Bright, 2005). Pollock (2005) found that IA children, regardless of country of origin, acquired their first 50 words at a relatively matched pace.…”
Section: Language Contentmentioning
confidence: 98%
“…While the older children have the advantage of cognitive preparedness, they also have further gains to make in order to catch up with their same age peers. Furthermore, vocabulary skills continue to be strengths for IA children 5 years after adoption (Glennen & Bright, 2005).…”
Section: Language Contentmentioning
confidence: 99%